National and international agricultural research and rural poverty: the case of rice research in India and China - Fan, Shenggen; Chan-Kang, Connie (Wiley, 2005)
We measure the total benefits from rice varietal improvement research in China and India, using variety adoption and performance data over the last two decades. Genetic or pedigree information is used to partition the total benefits between these two countries and International Rice Research Institute (IRRI). Finally, reported elasticities of poverty reduction with respect to agricultural output growth are used to assess the effects of national and international research on poverty reduction in rural India and China. The results indicate that rice varietal improvement research has contributed tremendously to increase in rice production, accounting for 14% to 24% of the total production value over the last two decades in both countries. Rice research has also helped reduce large numbers of rural poor. IRRI played a crucial role in these successes. In 1999, for every US$1 million invested at IRRI, more than 800 and 15,000 rural poor were lifted above the poverty line in China and India, respectively. These poverty reduction effects were even larger in the earlier years.